Ireland's gramophones : material culture, memory, and trauma in Irish modernism - Cammack, Zan (Clemson University Press, 2021)
"Ireland's Gramophones examines the perpetual presence of the gramophone in literature of Irish modernism: the same period in which gramophonic technology grew to cultural prominence. The book argues that the gramophone, as object and instrument, embodies accounts of a culture frequently traumatized through violence and disruption"-- Provided by publisher
Keywords: Phonograph in literature.; English literature -- Irish authors -- History and criticism.; Modernism (Literature) -- Ireland.; Collective memory in literature.; Littérature anglaise -- Auteurs irlandais -- Histoire et critique.; Modernisme (Littérature) -- Irlande.; Mémoire collective dans la littérature.; Social & cultural history.; History -- Europe -- Ireland.; Collective memory in literature; English literature -- Irish authors; Modernism (Literature); Phonograph in literature; Ireland; Irish Modernism; gramophones; Thing theory; cultural studies; trauma; Criticism, interpretation, etc.; Literary criticism; Literary criticism.; Critiques littéraires.